2017
DOI: 10.1515/afe-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Alloys Smelting in Shaft- Reverberatory Furnaces in a Liquid Bath Mode

Abstract: The aim of research was creation of a furnace for aluminum alloys smelting "in a liquid bath" in order to reduce metal loss. In the paper, the author demonstrates the results of research on smelting of aluminum alloys in a shaft-reverberatory furnace designed by the author. It has been shown that smelting aluminum alloy in a liquid bath was able to significantly reduce aluminum loss and that shaft-reverberatory design provided high efficiency and productivity along with lower energy costs. Ensuring continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Computer modelling of the melting and refining processes of aluminium alloys is a challenging precondition for manual design and soft learning of better furnaces, which has attracted the attention of researchers [1]. With modelling and simulations, it has been demonstrated that the behaviour of aluminium alloys in its liquid phase processed in a reverberatory furnace can be shaped by setting initial points on design variables [2]. The results obtained by Heugenhauser, Kaschnitz and Schumacher [3] have been favourably used for determining optimal process parameters in numerous areas such as the aerospace industry, the transport industry and materials manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Computer modelling of the melting and refining processes of aluminium alloys is a challenging precondition for manual design and soft learning of better furnaces, which has attracted the attention of researchers [1]. With modelling and simulations, it has been demonstrated that the behaviour of aluminium alloys in its liquid phase processed in a reverberatory furnace can be shaped by setting initial points on design variables [2]. The results obtained by Heugenhauser, Kaschnitz and Schumacher [3] have been favourably used for determining optimal process parameters in numerous areas such as the aerospace industry, the transport industry and materials manufacturing.…”
Section: Introductionmentioning
confidence: 99%